2010
DOI: 10.1364/ao.49.004846
|View full text |Cite
|
Sign up to set email alerts
|

Loss-reduced photonic liquid-crystal fiber by using photoalignment method

Abstract: We present a loss-reduced photonic liquid-crystal fiber (PLCF) using the noncontact photoalignment method. The photoexcited and adsorbed azo dye on the capillary surface of a PLCF induces uniform and highly ordered orientation of the liquid crystal (LC). The anchoring force of the photoalignment effect is combined with that generated by surface boundary conditions of the photonic crystal fiber (PCF). Transmission loss resulting from LC scattering can be reduced from -2.8 to -1.3 db/cm within 10 min. This photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Before filling with the respective FLC, the capillaries were prepared to promote parallel LC alignment. Because the inner surfaces of the cavity were not available for mechanical treatment, it was necessary to use treatment of photosensitive compounds (either polymer precursors or azo dyes) with linearly polarized radiation for this purpose. Previous experiments indicated that this nonintrusive method works well for capillaries and optical fibers. , Here, we used the azo dye brilliant yellow (BY) and applied a method described by Ertman and co-workers . For this purpose, a solution of 2% BY in hexane was filled into the capillary, the sample was heated to 140 °C for 20 min, and then excess solution was removed under a nitrogen stream of approximately 2 bar.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Before filling with the respective FLC, the capillaries were prepared to promote parallel LC alignment. Because the inner surfaces of the cavity were not available for mechanical treatment, it was necessary to use treatment of photosensitive compounds (either polymer precursors or azo dyes) with linearly polarized radiation for this purpose. Previous experiments indicated that this nonintrusive method works well for capillaries and optical fibers. , Here, we used the azo dye brilliant yellow (BY) and applied a method described by Ertman and co-workers . For this purpose, a solution of 2% BY in hexane was filled into the capillary, the sample was heated to 140 °C for 20 min, and then excess solution was removed under a nitrogen stream of approximately 2 bar.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As displayed in Fig. 11.2, it has been successfully applied to align LCs in photonic crystal fibers so as to reduce scattering loss and improve their optical performance [61,62]. LC configuration can be controlled by varying the photoirradiation.…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%